Complications of Transcatheter Arterial Chemoembolization for Treatment of Primary Liver Cancer - Novelli, Paula M.; Gustafson, Christopher; Orons, Philip D. (Digestive Disease Interventions, 2023)
Transcatheter arterial chemoembolization (TACE) is the standard practice in treating both primary and metastatic liver neoplasms. TACE is a practical, minimally invasive procedure involving the delivery of chemotherapeutic agents into the artery supplying a tumor while simultaneously embolizing its blood supply. This approach can be used for curative and palliative intent across multiple cancer types. Historically, TACE has been instrumental in the treatment algorithms for hepatocellular carcinoma, allowing patients with unresectable disease to be downstaged and to slow disease progression, affording opportunities for transplantation and increased survival. Although benefits of TACE include lower morbidity and mortality versus systemic chemotherapy and surgical approaches, the procedure has risks and complications. Interventional radiologists and physicians involved in the care of these patients should be aware of the associated complications including avoidance and treatment strategies.
Keywords: hepatocellular carcinoma; transarterial chemoembolization; transcatheter locoregional therapy; complications